Quizizz Formative Assessment For Detecting Elementary Mathematics Misconceptions: Asesmen Formatif Quizizz Untuk Mendeteksi Miskonsepsi Matematika Sekolah Dasar - Irma Jayanti; Retno Nuzilatus Shoimah; Moh. Vito Miftahul Munif (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The rapid integration of digital technology has fundamentally transformed educational evaluation practices. Specific Background Within foundational education, continuous evaluation plays a vital role in identifying student errors early, allowing educators to provide immediate instructional feedback. Knowledge Gap Despite widespread adoption, existing research regarding the utility of gamified platforms as a diagnostic instrument for identifying numerical miscalculations remains highly fragmented and lacks a comprehensive synthesis. Aims This systematic literature review utilizes the PRISMA 2020 guidelines to analyze the characteristics, practical application, strengths, and technological limitations of digital evaluations in identifying cognitive errors among young learners. Results Thematic analysis of fifteen selected articles reveals that this digital platform successfully identifies student error patterns through real-time learning analytics and automated feedback mechanisms, while simultaneously increasing motivation. Novelty This review uniquely synthesizes fragmented studies to establish gamified applications not merely as interactive evaluation tools, but as dedicated diagnostic instruments for early error detection in foundational numerical concepts. Implications The findings mandate comprehensive teacher training in digital diagnostic design and urge policymakers to address technological infrastructure disparities to optimize digital evaluation practices. Highlights Interactive digital platforms significantly boost student motivation and active engagement during learning evaluations. Real-time analytical reports enable educators to quickly identify unmastered learning indicators. Technological infrastructure constraints and inadequate digital literacy hinder the full implementation of diagnostic tools. Keywords Systematic Literature Review; Diagnostic Instrument; Learning Analytics; PRISMA Guidelines; Educational Technology